2020
DOI: 10.3389/fmicb.2020.01739
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characteristics and Potential Metabolic Adaptations of Hadal Trench Roseobacter and Alteromonas Bacteria Based on Single-Cell Genomics Analyses

Abstract: Heterotrophic bacteria such as those from the Roseobacter group and genus Alteromonas dominate the hadal zones of oceans; however, we know little about the genomic characteristics and potential metabolic adaptations of hadal trench-dwelling bacteria. Here, we report multiple single amplified genomes (SAGs) belonging to Roseobacter and Alteromonas, recovered from the hadal zone of the Mariana Trench. While phylogenetic analyses show that these hadal SAGs cluster with their surface relatives, an analysis of geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 120 publications
1
4
0
Order By: Relevance
“…However, to our knowledge, there are few marine bacteria that have been reported to be responsible for the formation of struvite. As mentioned above, the genus Alteromonas comprises versatile microorganisms playing essential roles in marine biogeochemical cycles (Lelchat et al, 2015;Chen et al, 2020;Cusick et al, 2021;Gago et al, 2021). In this study, we suggest that Alteromonas spp.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, to our knowledge, there are few marine bacteria that have been reported to be responsible for the formation of struvite. As mentioned above, the genus Alteromonas comprises versatile microorganisms playing essential roles in marine biogeochemical cycles (Lelchat et al, 2015;Chen et al, 2020;Cusick et al, 2021;Gago et al, 2021). In this study, we suggest that Alteromonas spp.…”
Section: Discussionsupporting
confidence: 56%
“…Prevalence analysis of ammonification metabolism pathways suggested that ammonium production was ubiquitous among the genus Alteromonas. Considering Alteromonas is indigenous in marine environments and has adapted to high salinity (Ivars-Martinez et al, 2008;Gonzaga et al, 2012;Chen et al, 2020;Gago et al, 2021), it is reasonable to question the role of Alteromonas spp. in struvite deposition in the ocean and sea.…”
Section: Discussionmentioning
confidence: 99%
“…The variable part of the pan-genome relates to the accessory or unique features, common to several or limited to individual strains, respectively, and associates with metabolic variability and ecological differentiation within the species or population, resulting in “microdiversity” of phenotypic traits [ 40 , 50 , 51 ]. It is interesting that each of the P. distincta and P. arctica A 37-1-1 T genomes contain from 7 to 210 unique genes, the orthologues of which are absent in other Pseudoalteromonas genomes ( Figure 4 and Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some desirable physiological and biochemical features such as aerobic anoxygenic photosynthesis, degradation of aromatics, quorum sensing and other characteristics [4] have been found in the Roseobacter group, which are widely distributed in marine ecosystems, including coastal zones, hydrothermal vents and sediments. The species of the Roseobacter group were shown to share 89 % 16S rRNA gene sequence similarity [5–7]. Wirth et al suggested that the 16S rRNA gene showed poor resolution of phylogenetic relationships among this group [8].…”
Section: Full-textmentioning
confidence: 99%